Pomoc humanitarna a nowe ruchy religijne: „humanitarni wolontariusze” organizacją charytatywną kościoła scjentologicznego. „Coś można z tym zrobić”. - Anoszko, Sergiusz (Studia Europaea Gnesnensia, 2019)
The article discusses religious humanitarian aid on the example of the Vol-unteer Ministers, an organization attached to the Church of Scientology. The core issue here is the controversy surrounding the activities and the social aftermath of that structure. By examining particular instances, including their activities in Poland, the author attempts a preliminary explanation of the problem and remarks on the allegations made with respect to scientologists.